2006
DOI: 10.1128/jb.00606-06
|View full text |Cite
|
Sign up to set email alerts
|

Type III Pilus of Corynebacteria: Pilus Length Is Determined by the Level of Its Major Pilin Subunit

Abstract: Multiple pilus gene clusters have been identified in several gram-positive bacterial genomes sequenced to date, including the Actinomycetales, clostridia, streptococci, and corynebacteria. The genome of Corynebacterium diphtheriae contains three pilus gene clusters, two of which have been previously characterized. Here, we report the characterization of the third pilus encoded by the spaHIG cluster. By using electron microscopy and biochemical analysis, we demonstrate that SpaH forms the pilus shaft, while Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 32 publications
1
102
0
Order By: Relevance
“…The general principles of assembly were first established through studies on the SpaA pili expressed by Corynebacterium diphtheriae. These pili, encoded by the gene cluster spaA-spaB-srtA-spaC, comprise a polymeric shaft formed by SpaA, SpaC located at the tip, and SpaB found at the base and occasionally along the shaft (6,(8)(9)(10). In our current model, successive major pilin SpaA subunits are joined by the action of the pilus-specific sortase SrtA.…”
mentioning
confidence: 99%
“…The general principles of assembly were first established through studies on the SpaA pili expressed by Corynebacterium diphtheriae. These pili, encoded by the gene cluster spaA-spaB-srtA-spaC, comprise a polymeric shaft formed by SpaA, SpaC located at the tip, and SpaB found at the base and occasionally along the shaft (6,(8)(9)(10). In our current model, successive major pilin SpaA subunits are joined by the action of the pilus-specific sortase SrtA.…”
mentioning
confidence: 99%
“…Each fimbrial gene cluster is composed of at least one pilin-specific sortase gene (srtA to -E) and three sortase-mediated pilus assembly genes (spaA to -I). Morphological and genetic studies have clearly demonstrated that each pilus of C. diphtheriae is composed of three pilin subunits and that the pilus assembly process requires pilin-specific sortases (60,141,417,435,436). Thus, the genomic islands contribute substantially to the structure of the cell surface.…”
Section: Dna Regions In the C Diphtheriae Genome Acquired By Hgtmentioning
confidence: 99%
“…Five contain phage-related genes and may be prophage remnants. Several pathogenicity-related functions are encoded in the genomic islands, including a siderophore biosynthesis and export system and a potential lantibiotic biosynthesis system, as well as three sortase-related fimbrial systems (60,141,417,436). Each fimbrial gene cluster is composed of at least one pilin-specific sortase gene (srtA to -E) and three sortase-mediated pilus assembly genes (spaA to -I).…”
Section: Dna Regions In the C Diphtheriae Genome Acquired By Hgtmentioning
confidence: 99%
“…A nonexhaustive number of pilus gene clusters also described in the literature and/or present in sequence databases were retrieved manually, i.e. L. rhamnosus (4), Corynebacterium glutamicum (26) (41,42) and C. diphtheriae (43)(44)(45). Their C-terminal domains were subsequently analyzed with the MEME suite (25).…”
Section: Methodsmentioning
confidence: 99%